1996
DOI: 10.1042/bj3140993
|View full text |Cite
|
Sign up to set email alerts
|

Natural-product inhibitors of human DNA ligase I

Abstract: Enzymatic activity mediated by recombinant human DNA ligase I (hLI), in conjunction with tannin removal procedures, has been applied to a natural-product screen involving approximately 1000 plant extracts and various pure compounds. The primary hLI activity assay involved the measurement of the amount of radiolabelled phosphate in a synthetic nucleic acid hybrid that becomes resistant to alkaline phosphatase as a result of ligation. A bioactivity-guided fractionation scheme resulted in the isolation of ursolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 35 publications
0
27
0
1
Order By: Relevance
“…Protolichesterinic acid was able to induce apoptosis through a caspase-dependent pathway in androgen-sensitive (LNCaP) and androgen-insensitive (DU-145) human prostate cancer cells [9] and in HeLa cells [10]. In in vitro assays, protolichesterinic acid showed inhibitory action against 5-lipoxygenase from porcine leucocytes [11], platelet-type 12-lipoxygenase [12], human DNA ligase I [13] and DNA polymerase of HIV-1 reverse transcriptase [14]. In the last years, many studies demonstrated that some natural products exhibited a synergic antitumour effect with conventional chemotherapeutic agents [15][16][17][18].…”
Section: Introductionmentioning
confidence: 98%
“…Protolichesterinic acid was able to induce apoptosis through a caspase-dependent pathway in androgen-sensitive (LNCaP) and androgen-insensitive (DU-145) human prostate cancer cells [9] and in HeLa cells [10]. In in vitro assays, protolichesterinic acid showed inhibitory action against 5-lipoxygenase from porcine leucocytes [11], platelet-type 12-lipoxygenase [12], human DNA ligase I [13] and DNA polymerase of HIV-1 reverse transcriptase [14]. In the last years, many studies demonstrated that some natural products exhibited a synergic antitumour effect with conventional chemotherapeutic agents [15][16][17][18].…”
Section: Introductionmentioning
confidence: 98%
“…There have been several attempts to identify DNA ligase inhibitors by screening of synthetic chemical and natural product libraries that have met with limited success. These have mainly involved radioactive-based assays and the screening of a relatively small number of compounds [79]. A series of small molecule inhibitors with differing specificities for the three human DNA ligases were identified by a structure-based approach using the atomic resolution structure of the DNA binding domain of human DNA ligase I complexed with nicked DNA [2,10].…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that, although the same enzyme active site may be involved in both enzyme adenylation and DNA relaxation, inhibitors may exert allosteric effects by inducing conformational changes that disrupt only one of these activities. Studies with inhibitors are important for the assignment of specific cellular functions to these enzymes, as well as for their development into clinically useful antitumour agents [54].…”
Section: Anti-tumor Activity Of a 3-oxo Derivative Of Oleanolic Acidmentioning
confidence: 99%